2017
DOI: 10.3762/bjnano.8.68
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of single-wall carbon nanotubes with supramolecular Congo red – properties of the complexes and mechanism of the interaction

Abstract: A method of dispersion of single-wall carbon nanotubes (SWNTs) in aqueous media using Congo red (CR) is proposed. Nanotubes covered with CR constitute the high capacity system that provides the possibility of binding and targeted delivery of different drugs, which can intercalate into the supramolecular, ribbon-like CR structure. The study revealed the presence of strong interactions between CR and the surface of SWNTs. The aim of the study was to explain the mechanism of this interaction. The interaction of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…All analyses have shown that CR binding to the surface of the carbon nano- [34]. The TEM, SEM and AFM images of the SWNT-CR complexes confirm that the interaction between CR and carbon nanotube surface is based on the "face to face" stacking.…”
Section: The Interaction Of Congo Red With Carbon Nanotubesmentioning
confidence: 70%
See 4 more Smart Citations
“…All analyses have shown that CR binding to the surface of the carbon nano- [34]. The TEM, SEM and AFM images of the SWNT-CR complexes confirm that the interaction between CR and carbon nanotube surface is based on the "face to face" stacking.…”
Section: The Interaction Of Congo Red With Carbon Nanotubesmentioning
confidence: 70%
“…7.6). This effect is related to the change in the electron structure of the CR molecule after binding to carbon nanotubes and is explained by the transition of the CR molecule to the quinoid form [34,38]. A similar phenomenon is described in the case of binding CR to the surface of graphene oxide [32].…”
Section: The Interaction Of Congo Red With Carbon Nanotubesmentioning
confidence: 82%
See 3 more Smart Citations